THE STUDENTS' SELF-ESTEEM ON THEIR SPEAKING ABILITY - Azhari, Ahlam; Muhayyang, Maemuna; Ariyani, Amra (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This article aimed to determine whether there is a correlation between self-esteem and students’ speaking ability at SMAN 4 Takalar. The study employed a correlational research design. The subjects were 28 twelfth-grade students from class XII MIA 6 at SMAN 4 Takalar during the 2024/2025 academic year, selected through cluster random sampling to collect the necessary data. The data were gathered using a questionnaire and a speaking test. Based on the results of the self-esteem questionnaire, 23 students (82.14%) demonstrated a high level of self-esteem, while 5 students (17.86%) showed a low level. The speaking test results indicated that 12 students (42.86%) performed poorly, and 16 students (57.14%) performed very poorly. The correlation coefficient between students’ self-esteem and their speaking ability was found to be 0.515, which falls within the moderate category. Since the rxy value (0.515) exceeded the rtable value (0.373), the alternative hypothesis was accepted. In conclusion, students’ self-esteem significantly influences their speaking ability at SMAN 4 Takalar. These findings suggest a meaningful correlation between self-esteem and speaking performance. To effectively boost students’ confidence, teachers are encouraged to create a supportive classroom atmosphere, utilize consistent positive reinforcement, and offer frequent speaking opportunities in a nonjudgmental environment with engaging activities.